2009
DOI: 10.1354/vp.08-vp-0218-s-fl
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cancer Stem Cells in Dog Glioblastoma

Abstract: There is increasing evidence in some malignancies that the tumor clone is heterogeneous in regard to proliferation and differentiation. The cancer stem cell hypothesis implies that not all the cells in the tumor have the same capacity to proliferate and maintain the growth of the tumor. Only a relatively small fraction of cells in the tumor, termed cancer stem cells (CSCs), possess the ability to proliferate and self-renew extensively. In the past decade, several groups have reported the existence of a CSC pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 45 publications
3
62
0
4
Order By: Relevance
“…Targeting either stem cell surface markers or dysregulated “developmental” pathways in tumors is an attractive and ongoing area of research. Stem‐like cells expressing putative developmental markers such as CD133, Olig2, and nestin have been described by several authors in canine gliomas (Fig 4), and preliminary data suggest that epigenetic alterations in canine glioma may parallel the developmental profile seen in human tumors 219, 220, 221, 222, 223. An alternative utilization of stem cells in neurooncology is the exploitation of the inherent tumor‐tropic properties of normal or modified stem cells.…”
Section: Novel Therapiesmentioning
confidence: 65%
“…Targeting either stem cell surface markers or dysregulated “developmental” pathways in tumors is an attractive and ongoing area of research. Stem‐like cells expressing putative developmental markers such as CD133, Olig2, and nestin have been described by several authors in canine gliomas (Fig 4), and preliminary data suggest that epigenetic alterations in canine glioma may parallel the developmental profile seen in human tumors 219, 220, 221, 222, 223. An alternative utilization of stem cells in neurooncology is the exploitation of the inherent tumor‐tropic properties of normal or modified stem cells.…”
Section: Novel Therapiesmentioning
confidence: 65%
“…13,23,44 This protein was recently reported in vascular endothelial cells of canine FFPE. 55 Using the same antibody, we detected CD34 expression in endothelial cells in a various canine and feline tissues. Interestingly, this marker is not expressed in human peripheral nerve sheath tumors (eg, neurofibromas, schwannomas).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study in human medicine have proposed a novel strategy for the treatment of cancer targeted at CSCs, and notable results have been presented regarding CSCs from basic and clinical trials (28). Veterinary medicine follows human medicine, and CSCs have been reported from various types of solid tumor and hematological malignancies (29)(30)(31)(32). To the best of our knowledge, the current study is the first to describe CSCs identified by rhodamine in a canine cancer cell line, and it may lead to basic studies regarding cHCSC-targeting treatment.…”
Section: Discussionmentioning
confidence: 99%